An application of modified Logistic and Gompertz growth models in Japanese quail - F UCKARDES; D NARINC (Indian Journal of Animal Sciences, 2014)
Growth functions describe body weight changes over time, allowing information from longitudinal measurements to be combined into a few parameters with biological interpretation. The Gompertz and Logistic models, which have three parameters (A: asymptotic body weight, b: shape parameter,c: constant of average growth rate), have been used extensively in poultry species to describe the development of body weight. The first aim of this study was to gain new two parameters that are called hatching body weight (λ) and maximum growth rate (μ) these parameters which are important for animal breeding to the Logistic and Gompertz models respectively. Furthermore, the second aim of this study was to reveal similarities and differences of both models in growth data of Japanese quail by using various goodness of fit criteria and residual analysis.The growth data of 64 mixed sex Japanese quail consisted of individual live weights of 3-day intervals from hatching (day 0) to 42 days of age. The parameters λ, A and μ of the Gompertz and Logistic models were estimated as, 8.71, 242.10, 6.00 g and 14.71, 208.44, 6.50 g, respectively. As a result of the goodness of fit criteria and residuals analysis, the Gompertz model indicates a much better fit than the Logistic model to Japanese quail data set. According to the results, transformed Gompertz and Logistic models are not only more profitable for poultry species but also more useful for other livestock species such as goat, sheep and cattle.